Human Rights Discourse in the Sustainable Development Agenda Avoids Obligations and Entitlements Comment on "Rights Language in the Sustainable Development Agenda: Has Right to Health Discourse and Norms Shaped Health Goals?" - Carmel Williams; Alison Blaiklock (Kerman University of Medical Sciences, 2016)
Our commentary on Forman et al paper explores their thesis that right to health language can frame global health policy responses. We examined human rights discourse in the outcome documents from three 2015 United Nations (UN) summits and found rights-related terms are used in all three. However, a deeper examination of the discourse finds the documents do not convey the obligations and entitlements of human rights and international human rights law. The documents contain little that can be used to empower the participation of those already left behind and to hold States and the private sector to account for their human rights duties. This is especially worrying in a neoliberal era.